Differences according to sex in patients admitted to intensive care units - Julio César González Aguilera; Jorge Omar Cabrera Lavernia; Yoleinis Esperanza Vázquez Belizón; Armando Arias Ortiz (Centro Provincial de Información de Ciencias Médicas, 2023)
Introduction: Nowadays disparities as for sex in patients with serious diseases can be found, which has not been explained in the clinical-epidemiological studies carried out until the moment. Objective: To identify the differences according to sex in patients admitted to intensive care units. Methods: An observational and prospective study of 187 patients admitted to the Intensive Care Units of Carlos Manuel de Céspedes Provincial General Hospital was carried out in Granma that included the months of November and December, 2018-2020. Among the analyzed variables we can mention: age, sex, origin, diagnosis at admission, state when discharged from the unit, hospital stay, syndrome of systemic inflammatory response, stage of the sepsis, risk factors, community acquired infections and required treatment. Results: In the investigation most of the patients corresponded to female sex (60.9 %) and the mean age was 31.6 and 49.6 years in women and men, respectively (p=0.000). Also, significant differences existed as for the origin (p=0.012) and the initial diagnoses (p=0.018); while the average of the APACHE II was 7.2 in women and 11.6 in men (p=0.000) and the Sequential Organ Failure Assessment Score had a mean of 0.7 and 2.0, in that same order (p=0.000). Conclusions: The patients of male sex presented average age, diagnosis, origin, seriousness and dysfunction of organs significantly different to those of female sex. Although disparities were not appreciated as for risk factors and infections associated with the community, the frequency of men that require treatment was significantly higher.